Coseismic electric and magnetic signals observed during 2017 Jiuzhaigou Mw 6.5 earthquake and explained by electrokinetics and magnetometer rotation. Issue 2 (27th August 2020) - Gao, Yongxin; Zhao, Guoze; Chong, Jiajun; Klemperer, Simon L; Han, Bing; Jiang, Feng; Wen, Jian; Chen, Xiaobin; Zhan, Yan; Tang, Ji; Xiao, Qibin; Wang, Lifeng
SUMMARY: Very clear coseismic electric and magnetic signals accompanying seismic waves were observed during the 2017 M w 6.5 Jiuzhaigou earthquake, which took place in western China. In order to understand the generation mechanism of these observed signals, we simulate electric and magnetic responses to this specific earthquake based on three mechanisms, namely, the electrokinetic effect, the motional induction effect and the rotation effect of the coil-type magnetometer. We conduct the simulations using a point source model and a realistic layered earth model and compare to the observed data in the frequency band 0.05–0.3 Hz. Our results show that the electrokinetic effect can explain the observed electric fields in both waveform and amplitude, but it cannot explain the magnetic signals accompanying the Rayleigh wave. The motional induction effect cannot explain either the coseismic electric or magnetic data because it predicts much weaker coseismic electric and magnetic fields than the observed data. The magnetic fields resulting from the rotation of the magnetometer agree with the observed data in the waveforms though their amplitudes are two to four times smaller than the observed data. Our simulations suggest that the electrokinetic effect is responsible for the generation of coseismic electric fields and that rotation of the coil magnetometer is likely the main cause of coseismic magnetic fields. The results improve our interpretation of the coseismic electromagnetic (EM) phenomenon and are useful for understanding other kinds of earthquake-associated EM phenomena.